Al‐neal Degrades Al2O3 Passivation of Silicon Surface. Issue 23 (18th July 2021) - Setälä, Olli E.; Pasanen, Toni P.; Ott, Jennifer; Vähänissi, Ville; Savin, Hele
Abstract : Atomic layer deposited (ALD) aluminum oxide (Al2 O3 ) has emerged as a useful material for silicon devices due to its capability for effective surface passivation and ability to generate p + region underneath the oxide as active or passive component in semiconductor devices. However, it is uncertain how Al2 O3 films tolerate the so‐called Al‐neal treatment that is a necessary process step in devices that also contain silicon dioxide (SiO2 ) passivation layers. Herein, it is reported that the Al‐neal process is harmful for the passivation performance of Al2 O3 causing over eightfold increase in surface recombination velocity (SRV) (from 0.9 to 7.3 cm s −1 ). Interestingly, it is also observed that the stage at which the so‐called activation of Al2 O3 passivation is performed impacts the final degradation strength. The best result is obtained when the activation step is done at the end of the process together with the Al‐neal thermal treatment, which results in SRV of 1.7 cm s −1 . The results correlate well with the measured interface defect density, indicating that the Al‐neal affects defects at the Si/SiO x /Al2 O3 interface. The root causes for the defect reactions are discussed and possible reasons for the observed phenomena are suggested. Abstract : The harmful impact of the Al‐neal process on passivation performance of Al2 O3 is reported. The stage at which the so‐called activation of Al2 O3 passivation is performed is observed to have a major effect on the passivation. The best result is achieved by omitting the separate activation step. Finally, the underlying causes for observations are discussed.